Performance Tuning Towards a KVM-Based Low Latency Virtualization System - Baojing Zuo; Kai Chen; Alei Liang; Haibing Guan; Jun Zhang; Ruhui Ma; Hongbo Yang (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
Utilizing virtualization technology to combine real-time operating system(RTOS)and off-the-shelf time-sharing general purpose operating system (GPOS)is attracting much more interest recently.Such combination has the potential to provide a large application base,and to guarantee timely deterministic response to real-time applications,yet there is no convincible experimental result about its real-time property.In this paper,we analyze the interrupt latency of RTOS running on Linux KVM based on some preliminary tunings,and find out System Management Interrupt (SMI) is the main factor which makes the maximum latency unideal, so we propose a method to limit the worst-case interrupt latency in an acceptable interval.Furthermore,we also find out that boosting priority may result in wastes of CPU resources when RTOS is not executing real-time tasks,so we design a co-scheduling mechanism to improve the CPU throughput of the GPOS system.